Assessing the impact of sectoral demand on environmental sustainability in Nigeria: An input-output analysis - Effiong, Mfonobong Okokon; Panicker, Manoj (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the relationship between sectoral demand and environmental sustainability in Nigeria using an input-output (I-O) analysis. Data were obtained from the Eurostat database. Results show that the fishing and mining sectors have the highest total effects and distributive effects on CO2eq emissions, indicating a high level of dependence on changes in sectoral consumption. The agricultural sector also has a significant impact on emissions, with a total effect of 0.0408 and a distributive effect of 0.0398. The study also analyzes output multipliers, income multipliers, and total income multipliers to understand the relationships between sectoral demand and economic growth. The results indicate that investing in sectors with high multipliers, such as mining and agriculture, can drive growth but also necessitate careful management to mitigate environmental impacts. The study suggests the need to adopt sustainable practices in key sectors to balance economic growth with environmental sustainability. Practical implications like developing policies and strategies to promote sustainable development in key sectors, investing in cleaner technologies and renewable energy to reduce emissions, promoting sustainable agriculture practices to reduce emissions and promote food security as well, and developing programs to educate and train stakeholders on sustainable development practices were identified for policymakers and practitioners.